Examination of attention, executive function, and memory as predictors of mortality risk in adults with systolic heart failure. (December 2019) - Gathright, Emily C; Dolansky, Mary A; Gunstad, John; Josephson, Richard A; Moore, Shirley M; Hughes, Joel W
Background: The prevalence and impact of cognitive impairment in heart failure is increasingly recognized. Converging evidence points to global cognitive function as predictive of prognosis in adults with heart failure when assessed with screening tools. Additional work is needed to understand which domains of cognitive function are most relevant for prognosis. Aims: The present study sought to examine associations between domains of cognitive function and mortality risk in adults with heart failure. Methods: In the present prospective, observational cohort study, global cognitive function, attention, executive function, and memory were assessed by means of a comprehensive neuropsychogical battery in adults with systolic heart failure. Mortality data were obtained from the National Death Index (median follow-up 2.95 years). Relationships among each cognitive domain and mortality were assessed with Cox regression. Covariates included age, sex, heart failure severity, comorbidity and depressive symptoms. Results: Participants were 325 patients with systolic heart failure with a mean age of 68.6 years (59% men, 73% Caucasian). Following covariate adjustment, better global cognitive function, attention, and executive function were related to decreased mortality risk. Conclusions: Future research is needed to clarify the underlying mechanisms of the association between cognitive impairment and mortality.